Video text detection - Lu, Tong (Advances in Computer Vision and Pattern Recognition, 2014)
Video text detection provides an efficient approach to the indexing, classification, retrieval and understanding of visual content. This unique text/reference presents a systematic introduction to the latest developments in video text detection. Opening with a discussion of the underlying theory and a brief history of video text detection, the text proceeds to cover pre-processing and post-processing techniques, character segmentation and recognition, identification of non-English scripts, techniques for multi-modal analysis, and performance evaluation. The detection of text from both natural video scenes and artificially inserted captions is examined. Various applications of the technology are also reviewed, from license plate recognition and road navigation assistance, to sports analysis and video advertising systems. Topics and features: Explains the fundamental theory in a succinct manner, supplemented with thorough, up-to-date references for further reading Highlights practical techniques to help the reader understand and develop their own detection systems and video text-based applications Discusses the state of the field from historical progress to the latest cutting-edge developments Serves as an easy-to-navigate reference, presenting the material in self-contained chapters Reviews the entire process from pre-processing to post-processing, including non-English script detection and advanced multi-modal techniques This accessible yet comprehensive overview of video text detection is essential reading for advanced students and researchers in pattern recognition, document analysis, image processing, video retrieval and related fields.